Ecological aspects and potential impacts of the non-native hydromedusa Blackfordia virginica in a temperate estuary. (15th October 2017) - Marques, Filipa; Angélico, Maria Manuel; Costa, José Lino; Teodósio, Maria Alexandra; Presado, Patrícia; Fernandes, António; Chainho, Paula; Domingos, Isabel
Abstract: The hydrozoan Blackfordia virginica has been reported over a wide geographical area, although it is mainly restricted to scattered records within estuarine areas of temperate and tropical regions. The aim of this study was to understand the spatial and temporal variability of an established population of this non-indigenous species on a temperate estuarine ecosystem, and its impacts over the plankton community. Sampling was conducted from 2011 to 2013 in the Mira estuary (Portugal) and higher densities were observed during the summer of 2013, with a maximum of 1689.3 medusae.m −3 . Spatially, higher abundances of medusae were associated with sites of higher abundance of oyster shells and higher percentage of hard substrate in the river bed. Smaller jellyfish were sampled in the vicinity of these hard substrate locations, suggesting these might be habitats for polyp fixation. A higher potential predation impact on the copepod population along the estuary was estimated for the summer of 2013, with a median half life of 6.1 days. Highlights: The population of the alien species Blackfordia virginica was studied in a estuary. Medusae were present during the warmer periods of the year. Higher abundances were recorded in locations near hard substrates in the river bed. Medusae potential predation impact was considered high during summer. This study presents the highest abundance ever recorded for this hydromedusa.